Policy Transfer and Instrument Constituency: Explaining the Adoption of Conditional Cash Transfer in the Philippines. Issue 3 (17th June 2019) - Saguin, Kidjie; Howlett, Michael
Abstract: Transnational policy transfer is a well‐documented phenomenon with studies from across many disciplines. However, the literature tends to over‐theorize but under‐operationalize what is transferred and how it is transferred. A significant issue in this regard concerns 'agency': that is, who is supplying and who is demanding policy lessons and examples. This paper highlights a relatively new concept in comparative policy studies, that of the 'instrument constituency', within the framework of transnational policymaking. It argues that instrument constituencies or groups of actors unified by their strong affinity with a specific policy tool are key agents in the transfer process, acting as suppliers and brokers of policy ideas, constantly searching to match their preferred solutions to policy problems. As this paper will show, incorporating such constituencies into policy transfer studies allows a better understanding of transfer as part of a sequential process of diffusion, and how knowledge about a policy instrument is assembled and transferred.